EFFECT OF CAPITAL ADEQUACY, LIQUIDITY, AND OPERATIONAL EFFICIENCY TO PROFITABILITY IN BANK SYARIAH MANDIRI (Period 2008 s.d. 2015) - Ismaulina, Ismaulina; Zulfadhli, Zulfadhli (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
This research aimed at analyzing the effects of Capital Adequacy (CAR), liquidity (FDR) and operational efficiency (BOPO) toward profitability (ROA) in PT. Bank Syariah Mandiri (2008 to 2015 Period). The effects of CAR, FDR and BOPO were measured quantitatively and correlated to the company’s ROA by means of double linear regression formula. The object of the research was three-monthly financial report through 31 observations. The findings showed that CAR and BOPO had negative and significant effects toward ROA. FDR had positive and no significant effects toward ROA. It was found that 94.6% of ROA could be explained by the variables of CAR, FDR and BOPO, while 5.4% could be explained by other variables which were not included in this research.